"Ending the Epidemic" Will Not Happen Without Addressing Racial/Ethnic Disparities in the United States Human Immunodeficiency Virus Epidemic. (19th May 2020) - Nosyk, Bohdan; Krebs, Emanuel; Zang, Xiao; Piske, Micah; Enns, Benjamin; Min, Jeong E; Behrends, Czarina N; Del Rio, Carlos; Feaster, Daniel J; Golden, Matthew; Marshall, Brandon D L; Mehta, Shruti H; et al.
Abstract: We estimated human immunodeficiency virus incidence and incidence rate ratios (IRRs) for black and Hispanic vs white populations in 6 cities in the United States (2020–2030). Large reductions in incidence are possible, but without elimination of disparities in healthcare access, we found that wide disparities persisted for black compared with white populations in particular (lowest IRR, 1.69 [95% credible interval, 1.19–2.30]).